ACCELERATING ENGLISH PROFICIENCY FOR ELEMENTARY SCHOOL STUDENTS THROUGH INTEGRATED SKILLS - Agnes Widyaningrum (Dinamika Bahasa dan Budaya, 2011)
English is a compulsory subject in Indonesia. The paradigm in teaching English is started at a very young age. Teaching English for young learners in Indonesia is challenging becuase the teachers have to adopt and adapt English and Indonesian cultures through the curriculum and other instruments used in teaching. Besides teaching materials, the teachers also asked to foster the students’ mastery in using English so that they can produce graduates who have good English competency. In line with the increasing demand of the graduates who are able to use English fluently, the policy makers are trying to improve better national curriculum in order that the school can apply it and keep it on the right track.   Key words: competency, teaching instruments, curriculum